2006
DOI: 10.1007/s10096-006-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

C6 peptide ELISA test in the serodiagnosis of Lyme borreliosis in Sweden

Abstract: The aim of this study was to evaluate the synthetic C6 peptide test as a first-line test in a two-tiered scheme for Borrelia serology in a clinically well-characterized population of patients with Lyme borreliosis in Kalmar County, Sweden. The study population consisted of a prospective group (n = 200), a control group (n = 255), and a retrospective group (n = 29). The test panel consisted of the Immunetics Quick ELISA C6 Borrelia assay kit (Immunetics, Cambridge, MA, USA), the Virotech Borrelia burgdorferi EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 14 publications
5
34
1
Order By: Relevance
“…All this together may explain why the seroprevalence was higher among the participants from the Åland Islands compared to the participants from South Central Sweden and from Southernmost Sweden. The seroprevalence in the TBD STINGstudy (20%) is within the range of those reported from other Europe-an studies: in healthy blood donors the seroprevalence ranged between 2 and 24% (Ekerfelt et al, 2001;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tjernberg et al, 2007;Tomao et al, 2005); in people living in endemic regions between 7 and 29% (Berglund & Eitrem, 1993;Carlsson et al, 1998;Gustafson et al, 1993b;Werner et al, 2001); and for people in high-risk groups (outdoor workers, orienteers and hunters) between 9 and 54% (Cetin et al, 2006;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tomao et al, 2005).…”
Section: Are There Gender-and Geographical Differences In the Borrelisupporting
confidence: 65%
“…All this together may explain why the seroprevalence was higher among the participants from the Åland Islands compared to the participants from South Central Sweden and from Southernmost Sweden. The seroprevalence in the TBD STINGstudy (20%) is within the range of those reported from other Europe-an studies: in healthy blood donors the seroprevalence ranged between 2 and 24% (Ekerfelt et al, 2001;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tjernberg et al, 2007;Tomao et al, 2005); in people living in endemic regions between 7 and 29% (Berglund & Eitrem, 1993;Carlsson et al, 1998;Gustafson et al, 1993b;Werner et al, 2001); and for people in high-risk groups (outdoor workers, orienteers and hunters) between 9 and 54% (Cetin et al, 2006;Fahrer et al, 1991a;Gustafson et al, 1993a;Hristea et al, 2001;Tomao et al, 2005).…”
Section: Are There Gender-and Geographical Differences In the Borrelisupporting
confidence: 65%
“…Although LB and multiple episodes of LB are primarily related to a certain part of the population with behavioural habits generating a higher risk of tick bites, the population which previously had LB will expand and may cause further difficulties that must be taken into account when interpreting borrelia serology. A known problem of borrelia serology in our area is a high seroprevalence (8-14%) in the healthy adult population most probably generated by a previous exposure to Borrelia with a persisting detectable antibody response for many years not related to clinical symptoms or signs (Tjernberg et al 2007). In this sense, seropositivity rates for all IR 6 peptides were indeed significantly higher in patients with self-reported previous LB as compared to those who did not report previous LB.…”
Section: Discussionmentioning
confidence: 65%
“…Patients with LB in Kalmar County in Sweden were prospectively included in a clinical study in 2003 (Tjernberg et al, 2007). Clinical data was recorded in a study protocol and serum samples were drawn at the first consultation (sample I), at 2-3 months (sample II) and 6 months (sample III), see Table 1 and Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C6 assay does not distinguish between IgG and IgM antibodies. Both assays have been described in previous publications from Scandinavian studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The C6 assay was implemented on a Bio-Rad Coda microplate processor, and the IDEIA ELISA was performed manually.…”
Section: Methodsmentioning
confidence: 99%